Gender, demand for agricultural credit and digital technology: Survey evidence from Odisha - Kramer, Berber; Pattnaik, Subhransu; Ward, Patrick S. (International Food Policy Research Institute, 2021)
This paper analyzes the potential linkages between innovations in agricultural credit and women’s empowerment. We provide survey evidence of lower baseline demand for agricultural credit among women than men. When asked to imagine that their financial institution would use data on past cultivation through observations of smartphone and satellite imagery to review loan applications and insure loans, women reported significantly more often than men that this would increase (and not decrease) the likelihood that they would apply for loans, and their desired loan amounts increased significantly more than those of men. Moreover, we find that the gender gap in demand for agricultural credit is explained, in part, by differences in empowerment between women and men, suggesting that increasing women’s empowerment could help bridge gender gaps in credit access and utilization. Using a cluster randomized trial, we assess whether gender sensitization has an effect on women’s empowerment and demand for credit, but we do not find that gender trainings help shift women’s empowerment or demand for credit. We conclude that improving access to digital credit is not going to be sufficient to empower women. Instead, gender responsive or gender transformative programming is required to improve demand and create an enabling environment in which norms are changed and make it easier for women to take out agricultural credit.